Consumer involvement as a covariant effect in rethinking the affective-cognitive relationship in advertising effectiveness - Vera, Jorge; Espinosa, Marco (Journal of Business Economics and Management, 2019)
The relationship between advertising effectiveness and behavioural intentions is assessed when involvement with the product is introduced as a direct covariant effect, rather than as a moderator. Advertising effectiveness is assessed through attitude towards the ad and advertising cognition. Advertising media type combined with age is tested as a moderating variable (younger/digital vs. older/traditional). With a sample of n = 307 consumers, a structural statistical path model is implemented to empirically test the hypotheses. It is found that involvement has an effect on attitude towards the ad and on ad cognition. Thus, it is established that the ad cognition variable, rather than attitude towards the ad, has a strong statistical effect on behavioural intentions. The model suggests that the level of the consumer’s attention to the ad depends on her/his degree of involvement with the product. Also, the evidence tends to indicate that the cognitive process through which the consumer builds purchase intentions is similar in both communication channels irrespective of age difference.